2020
DOI: 10.1111/jfb.14416
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niche partitioning of five skate species of genus Bathyraja in northern and central Patagonia, Argentina

Abstract: Overexploitation of marine communities can lead to modifications in the structure of the food web and can force organisms like elasmobranchs to change their feeding habits. To evaluate the impact that fisheries have on food webs and on the interactions between species, it is necessary to describe and quantify the diet of the species involved and follow it through time. This study compares the diet of five skate species using the data obtained from the by‐catch of the Argentine hake (Merluccius hubbsi) fishery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Here, socio-economic indexes were analyzed together, and it was found that fishing was one of the key drivers of the fish diversity decline in the Pearl River. Previous studies (focusing on fishery resources and fish communities) had reported that large dynamics of the fishery ecosystem in subtropical rivers and lakes were caused by overfishing, , and the response strategy of different ichthyological groups to overfishing events varied along with feeding structure and trophic level changes. During the past forty years, a steep decrease in fish and dietary organism diversity was observed in the Pearl River, which was consistent with the decrease in the fish, interaction density, and food web indexes (system omnivory index, Finn’s cycling index, and MPL ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, socio-economic indexes were analyzed together, and it was found that fishing was one of the key drivers of the fish diversity decline in the Pearl River. Previous studies (focusing on fishery resources and fish communities) had reported that large dynamics of the fishery ecosystem in subtropical rivers and lakes were caused by overfishing, , and the response strategy of different ichthyological groups to overfishing events varied along with feeding structure and trophic level changes. During the past forty years, a steep decrease in fish and dietary organism diversity was observed in the Pearl River, which was consistent with the decrease in the fish, interaction density, and food web indexes (system omnivory index, Finn’s cycling index, and MPL ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the trophic level and importance (PRP index) of the benthopelagic fish C. recurviceps decreased with the removal of the small-sized fish H. leucisculus in its major feeding structure. These results demonstrated that overfishing drove food web structure modifications and forced aquatic organisms to change their feeding habits, 35 such as the top predator Indo-Pacific humpback dolphins (Sousa chinensis) that reduced their consumption of high trophic-level prey due to an overfishinginduced prey decline. 36 Together with a fish biodiversity decline, a cascading top-down effect to lower trophic levels in aquatic ecosystems was also detected because overfishing produced a high-level predator reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fishing activities generally occur in the same waters inhabited by the species that consume the discards and discards often consist of prey naturally encountered and consumed. For example, broadnose skates ( Bathyraja brachyurops ) naturally feed on Argentinian hake ( Merliccius hubbsi ) and also consume post‐harvest waste from the Argentinian hake fishery in the same region (Tschopp et al ., 2020), therefore the physiological impacts noted for wildlife provisioned in tourism contexts may be greater than species that consume locally captured fishery discards. However, the rate at which discards of specific prey are produced may differ compared to when prey items are naturally hunted.…”
Section: Discussionmentioning
confidence: 99%
“…Despite most fishery discards sinking quantitative assessment is generally lacking for pelagic and benthic marine scavengers. Some evidence suggests that discards may contribute considerably to the diets and energy requirements of a range of species (e.g., 37% of the energetic requirements of invertebrate scavengers and hagfish in the North Sea (Catchpole et al, 2006), 10% of broadnose skate (Bathyraja brachyurops) diets in Patagonia (Tschopp et al, 2020) and 25%-78% to the diets of teleost fish in Japan (Yamamura, 1997; see also Lejeune et al, 2021). This suggests fishery discards likely have significant influence on marine food webs.…”
Section: Introductionmentioning
confidence: 99%
“…31 Then, discard consumers were identified by direct observation on fishing vessels 32 or by the presence of hake in the gut content of scavengers or opportunistic consumers. [33][34][35][36]…”
Section: Datamentioning
confidence: 99%